Effect of methyl position on the dynamic mechanical and shape‐memory properties of cresol‐based polybenzoxazines. Issue 42 (3rd July 2017) - Liu, Yanfang; Song, Shuning; Su, Xuehui; Wang, Aiqing; Shen, Shanshan; Li, Cuiyun
ABSTRACT: Three difunctional benzoxazines were synthesized from cresol isomers ( o ‐, m ‐, and p ‐methylphenols), 1, 3‐bis(3‐aminopropyl)‐1, 1, 3, 3‐tetramethyldisiloxane, and formaldehyde. The ring‐opening polymerization temperature decreases in the order of ortho ‐, para ‐, and meta ‐positions of methyl group for the benzoxazine monomers, whereas the glass transition temperature increases in the order of ortho ‐, para ‐, and meta ‐positions of methyl group for the resultant polybenzoxazines. In addition, the polybenzoxazines exhibit one‐way dual‐shape‐memory behavior in response to changes in temperature, and the shape‐memory effects are evaluated by tensile and bending tests with a temperature program based on glass transition temperature. The o ‐ and p ‐cresol‐based polybenzoxazines exhibit higher shape‐memory performance than their m ‐cresol‐based analogue/counterpart. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45443. Abstract :